(untitled) (KYAMC Journal, 2020)
Background : An epidemiological transition occurs during the turn of the 21 st century. Non- communicable diseasespredominate over the communicable diseases along with the global economic development. Among the non-communicable diseases, injuries and accidents become a major concern. Objectives: To identify the pattern of injuries prevailing in a rural community in Sirajganj district during 1st November 2015 to 31st January 2016, Materials and Methods: This cross sectional study was conducted among the people living in the rural area near to Shahjadpur Upazila Health Complex of Sirajganj. A total of 442 respondents were interviewed face-toface using a semi-structured questionnaire. Convenience sampling technique was adopted. Collected data were cleaned and analyzed with SPSS software (version 20.0). Results: There were 204 cases of injuries. Fall, cut injury, road traffic accident (RTA) and burn constituted 30.4%,30.4%,15.2% and 12.3% of the injuries respectively. Among the injured cases, 73 went to any health facility to seek treatment. Majority (53.4%) of the injured cases faced loss of activity with hand, 13.2% developed loss of mobility. Among the 73 injured persons who went to any healthcare facility for obtaining treatment, 2.7% expired, 4.1% lives with disability, 15.1% had temporary disability and 78.1% recovered. Nearly half (43%) of the respondents mentioned that they did not have idea about injury prevention. Conclusion: This study reiterates the need to spread the knowledge of pattern of injuries and its prevention through available evidence based strategies and multiple dissemination channels in rural areas. KYAMC Journal Vol. 11, No.-3, October 2020, Page 118-123